Highlights regarding the use of metallic nanoparticles against pathogens considered a priority by the world health organization - da Silva, Patricia Bento [UNESP]; Araújo, Victor Hugo Sousa [UNESP]; Fonseca-Santos, Bruno [UNESP]; Solcia, Mariana Cristina [UNESP]; Ribeiro, Camila Maringolo [UNESP]; da Silva, Isabel Cristiane [UNESP]; Alves, Renata Carolina [UNESP]; Pironi, Andressa Maria [UNESP]; Silva, Ana Carolina Lopes [UNESP]; Victorelli, Francesca Damiani [UNESP]; Fernandes, Mariza Aires [UNESP]; Ferreira, Paula Scanavez [UNESP]; et al. (Bentham Science Publishers, 2021)
The indiscriminate use of antibiotics has facilitated the growing resistance of bacteria, and this has become a serious public health problem worldwide. Several microorganisms are still resistant to multiple antibiotics and are particularly dangerous in the hospital and nursing home environment, and to patients whose care requires devices, such as ventilators and intravenous catheters. A list of twelve pathogenic genera, which especially included bacteria that were not affected by different antibiotics, was released by the World Health Organization (WHO) in 2017, and the research and development of new antibiotics against these genera has been considered a priority. The nanotechnology is a tool that offers an effective platform for altering the physical-chemical properties of different materials, thereby enabling the development of several biomedical applications. Owing to their large surface area and high reactivity, metallic particles on the nanometric scale have remarkable physical, chemical, and biological properties. Nanoparticles with sizes between 1 and 100 nm have several applications, mainly as new antimicrobial agents for the control of microorganisms. In the present review, more than 200 reports of various metallic nanoparticles, especially those containing copper, gold, platinum, silver, titanium, and zinc were analyzed with regard to their anti-bacterial activity. However, of these 200 studies, only 42 reported about trials conducted against the resistant bacteria considered a priority by the WHO. All studies are in the initial stage, and none are in the clinical phase of research.
Keywords: Bacterial resistance; Copper; Gold; Metallic nanoparticles; Nanotechnology; Platinum; Silver; Titanium; WHO priority list; Zinc